Komposisi Proksimat, Tingkat Kekerasan Dan Daya Terima Brownies Yang Dibuat Dengan Menggunakan Jenis Telur Yang Berbeda - Wahyuningsih, Sri, Pramudya Kurnia, STP, M.Agr, Rusdin Rauf, STP., MP (2014)
Background : The heeded of food is increase suitable to the increasing the number of inhabitant. The one of food that producted suitable to the quality and quantity is brownies. In making of brownies, the kind of egg is very important to determine structure, softer and stringer of brownies. Purpose : To know proximate composition the level of hard and acceptability brownies made by the different kind of egg. Methods : This research is experimental research that using brownies as an object and using different kind of egg ( chicken egg, duck egg and quail egg). The research is done at food laboratory of UMS and at laboratory engineer food of UGM. Methode of analyzing using statistical one way ANOVA test and followed DMRT (Duncan Multiple Range Test). Results : Quail egg brownies has the highest content of water (29,9%), duck egg brownies has the highest content of food powder (2,20%) and the highest content of fat (25,55%), chicken egg brownies has the highest content of protein (8,78%), the highest content of carbohydrate (2,36%), then the highest level of hard is quail egg (0,59%) and the most of acceptability color is duck egg (5,17). Conclusion : There is the different between proximate composition, the level of hard and acceptability of brownies with the using of different kind of egg ( chicken egg, duck egg, quail egg). Suggestion : By consideriny the proximate composition, the level of kekerasan and acceptability of brownies, it is suggested to use duck egg.